2019
DOI: 10.1186/s12885-019-6228-6
|View full text |Cite
|
Sign up to set email alerts
|

Systemic high-dose intravenous methotrexate in patients with central nervous system metastatic breast cancer

Abstract: BackgroundInfusion of high-dose intravenous methotrexate (MTX) has been demonstrating to penetrate the blood-brain barrier. The aim of this present study was to assess the efficacy and safety of high dose MTX in patients with central nervous system (CNS) metastases of breast cancer.MethodsTwenty-two patients with CNS metastases treated by MTX (3 g/m2) between April 2004 and October 2009 were enrolled. Clinical response rate, time to progression (TTP), overall survival (OS), and safety were assessed.ResultsIn t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Moreover, CBX2High cells were sensitive to methotrexate (Fig. 6B), a chemotherapeutic drug used in treatment of breast cancers [50]. However, effect of CBX7 on mTORC1 signaling did not correlate in terms of sensitivity to rapamycin as reflected in a [ Fig.…”
Section: Accepted Articlementioning
confidence: 99%
“…Moreover, CBX2High cells were sensitive to methotrexate (Fig. 6B), a chemotherapeutic drug used in treatment of breast cancers [50]. However, effect of CBX7 on mTORC1 signaling did not correlate in terms of sensitivity to rapamycin as reflected in a [ Fig.…”
Section: Accepted Articlementioning
confidence: 99%
“…Studies with metastatic breast cancer showed that patients tolerated i.v. administration of 3 g/m 2 to 3.5g/m 2 well and showed efficacy, claiming that MTX penetrates the blood-brain barrier if one administers such high doses, claiming that even higher doses of MTX could be administered [65,66]. Also, for Ara-C, studies with liposomal encapsulation of Ara-C demonstrated efficacy in patients with glioma and leptomeningeal metastasis [67].…”
Section: Discussionmentioning
confidence: 99%
“…It could impair ovarian reserve by targeting actively proliferating cells, including granulosa cells and oocytes 14 . While single low‐dose methotrexate used for the treatment of ectopic pregnancies had minimal impact on ovarian reserve, 15 the effects of higher doses at 3–16 g/m 2 , 16,17 or repeated doses, of methotrexate had not been well evaluated. Previous studies raised concerns about its gonadotoxicity, as iatrogenic menopause was reported in up to 68% of patients with breast cancers who received high‐dose methotrexate 18 .…”
Section: Discussionmentioning
confidence: 99%